How the french discovered the Lower depths - Serge Rolet (Studia Litterarum)
Despite the exceptional fame of Maxim Gorky in France since the very beginning of the 20 th century, the French public did not discover The Lower Depths until October 1905, later than other European countries. The competition between two translators, Eugène Séménoff and Élie Halpérine-Kaminski, lead to a lawsuit, which delayed the staging of the play for two years. Following the end of the trial, the play was immediately produced by Lugné-Poë at L’Œuvre Theatre; the press had advertised the play as the pinnacle of the theatrical season. The most noteworthy event was the performance on October 23, 1905 when Italian tragic actress Eleonora Duse played the part of Vassilissa in Italian, while other actors played their parts in French.